Approximation of a Function of Lip ( ξ (t), p ) Class by (C, 1) (N, pₙ) Method of its Fourier Series - Dhakal, Binod Prasad (Kathmandu University Journal of Science, Engineering and Technology, 2013)
In this paper, the degree of approximation of a function belonging to Lip ( ξ (t), p ) class by product summability method (C, 1) (N, pₙ) of its Fourier series has been determined